Pengaruh Media Video Tentang Pariwisata di Kabupaten Pesawaran Terhadap Peningkatan Pengetahuan Mahasiswa - Zainal, Anna Gustina (Jurnal Master Pariwisata (JUMPA), 2019)
This study uses realistic visualization in the form of photos which are the result of photographic elements, as well as visualization with infographic forms which are illustrative elements in visual communication design. the research uses True Experimental method with 2x2 factorial design and uses Pretest, Posttest, and Control Group Design. The purpose of this study is to examine the effect of visual presentation and language style through video media for increasing student knowledge and analyzing the most effective combination of messages on video media about tourism in Pesawaran District. From this research it is found that visual presentation and language style through video may influence improvement of student knowledge about tourism in Pesawaran Regency. All combinations of visual presentation and language style will influence knowledge improvement. Keywords: Video Media, Tourism, Pesawaran Regency